Restrictive measures on capital inflow in Brazil in the OTC derivative market: impact on non-financial firms - Lema, Salome Marie Alice (2016)
In August 2011, the Brazilian government taxed short positions in the foreign exchange (FX) derivative market in order to weaken the surge of post-crisis capital inflow, discourage carry trade strategies on the Real and avoid further local currency appreciation. Nevertheless, nonfinancial firms are also end-users of derivatives and might have suffered in case financial institutions transfer the regulatory cost to their clients in the real economy. To the extent that this tax increases the cost of hedging, firms may decide to hedge less, causing an increase in their exposure to currency risk. This paper aims at analysing if this regulatory change had an impact on Brazilian non-financial firms FX exposure, measured by the sensitivity of stock prices to currency fluctuation (FX-Beta). Therefore, it seeks to compare the FX beta of Brazilian non-financial listed firms before and after the implementation of the measure, to assess their degree of exposure to currency risk. In accordance with an increasing cost of hedging for those companies, results show that the beta difference also reached a riskier level.